Pengaruh Model Game Based Learning Terhadap Aktivitas dan Hasil Belajar Komputer Siswa Kelas V di SD Plus Marhamah - Putri, Rizki Maelta; Zuwirna, Zuwirna; Yeni J, Fetri; Hendri, Nofri (Indo-MathEdu Intellectuals Journal, 2024)
The variation of the game-based learning model and aims to determine its influence on the activities and learning outcomes of grade V students at SD Plus Marhamah. The research method applied in this study is quantitative with a quasy experiment design. The sampling technique uses purposive sampling. The sample was represented by class V.B as the control group and class V.C as the experimental group, each totaling 25 students. Data was collected through questionnaires for learning activities and tests for learning outcomes. Data analysis included normality test, homogeneity test, and t-test at a significance level of 0.05 to see the difference between the control group and the experiment. The results of the study showed that there was a significant influence of the application of the game-based learning model on student activities and learning outcomes. Based on this parametric statistical test (one tailed test), significant differences can be seen between the experimental class and the control class, both in activities and learning outcomes. Thus, it can be concluded that the game-based learning model has a positive and significant impact on the activities and learning outcomes of grade V students at SD Plus Marhamah